Exploring Language Teaching Methods: An in-Depth Analysis of Grammar Translation, Direct Method, and Audiolingual Method: A Literature Review - vireak keo; Bunrosy Lan (International Journal of Advance Social Sciences and Education (IJASSE), 2024)
The present literature study delves into the development of language teaching methodologies, with particular emphasis on three well-known techniques: Grammar Translation, Direct Method, and Audiolingual Method. The background underscores how pedagogical ideas have changed throughout time and stresses the historical context of language learning. The evaluation analyzes important academic publications, instructional resources, and empirical investigations using a thorough methodology to evaluate the advantages and disadvantages of each approach. Findings of the discussion show that educators can make informed decisions about selecting and adapting methodologies to optimize language instruction for diverse learner populations if they understand their historical development, theoretical underpinnings, practical implications, and limitations. This approach combines elements from each method while addressing their limitations, resulting in dynamic and effective language learning experiences that cater to diverse learner needs and goals. And the review concludes that Language teaching strategies vary, with each method having unique characteristics and methods. The Direct Method promotes natural language learning, the Audiolingual Method emphasizes habit building, and the Grammar Translation Method emphasizes formal language structures. To enhance effectiveness, teachers should combine technology, communicative teaching practices, and a learner-centered environment.